A quantitative amplitude of vagus nerve obtained by intraoperative neuromonitoring predicts postoperative vocal cord paralysis among patients in thyroid/parathyroid surgery as a second option - Hiroshi Katoh, MD, FACS; Riku Okamoto, MD; Kanako Naito, MD; Tomoya Mitsuma, MD; Mariko Kikuchi, MD; Takaaki Tokito, MD; Takeshi Naitoh, MD, FACS; Naoki Hiki, MD; Yusuke Kumamoto, MD; Takafumi Sangai, MD (Surgery Open Science)
Background: The advantage of intraoperative neuromonitoring (IONM) has been widely accepted in thyroid/parathyroid surgery. However, there are discrepancies of amplitudes on recurrent laryngeal nerve (RLN) palsy and vocal cord paralysis (VCP) because of amplitude variations among individuals. Accordingly, the universal usefulness of quantitative amplitude value per se among patients were assessed. Study design: IONM using a 4-step method (Vagus nerve (V1)-RLN (R1)-R2-V2) was applied to 777 RLNs (510 patients). Forty-nine RLNs were excluded because of either loss of signal without preoperative VCP or combined RLN resection. The remaining 728 RLNs were evaluated. The optimal cut-offs of amplitudes or ratios of amplitude decrease on VCP were determined and evaluated. An independent recent cohort (177 RLNs) was analyzed for validation. Results: Quantitative amplitudes of V2 or R2, and V2/V1 or R2/R1 ratio predicted VCP. The V2 of 117–216 μV predicted VCP with high (>80 %) sensitivity and specificity. Interestingly, the AUC of ROC curve of V2 was the highest, and a cut-off 124 μV of V2 most excellently predicted VCP with the highest sensitivity, specificity, and both positive and negative predictive values. In dissociative analyses, a V2 cut-off 124 μV still excellently predicted VCP in all ranges of initial V1 ≥ 100 μV. In a validation cohort, the V2 of 126–205 μV (cut-off 197 μV) predicted VCP with both high (>80 %) sensitivity and specificity. Conclusions: A quantitative V2 amplitude can predict postoperative VCP among individuals as a simple and a second option, that may be especially useful in some circumstances with unavoidable insufficient initial exposure of vagus nerve.